HUBUNGAN ANTARA KOMUNIKASI INTERPERSONAL DENGAN PENYESUAIAN SOSIAL PADA SISWA - Sulastri Saberina Bukit; Umbu Tagela; Yustinus Windrawanto (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2023)
Teenagers as social beings, have a great need to interact or socialize with other people. Social relations with other people are formed through the process of communication. Social adjustment as a process of self-adjustment takes place continuously, where in one's life one will be faced with two realities, namely self and the surrounding environment. Almost throughout a person's life always need other people to be able to interact with each other. This study aims to determine the relationship between interpersonal communication and social adjustment in XII students at SMK PGRI 1 Salatiga. This type of research is a quantitative research with a correlational approach to determine the relationship between the independent variables and the dependent variable. The population in this study were 117 students of SMK PGRI 1 Salatiga, who were taken using the cluster technique.correlation analysis Pearson with the help of the IBM SPSS Statistics 23. Based on the results of data analysis, it can be stated that there is a significant relationship between interpersonal communication and social adjustment of class XII students at SMK PGRI 1 Salatiga